RELEVANSI KISAH ASHABUL KAHFI DALAM TAFSIR AL-MARAGHI SEBAGAI JAWABAN TERHADAP KRISIS IDENTITAS GENERASI MILENIAL - Muhammad Arwani Rofi'i; Nurin Alfiani; Barda Royyan Hanafi (AL ITQAN: Jurnal Studi Al-Qur'an, 2023)
The identity crisis faced by the millennial generation is a central issue in social, psychological, and cultural development in this era of globalization. Many factors contribute to this identity crisis, including uncertainty about one's self-identity, shifting cultural values, and the impact of technological advancements and social media. This phenomenon often leads to confusion and difficulty in determining the direction of life, thus requiring a new approach to address this problem. This study aims to examine the relevance of the story of Ashabul Kahfi in Tafsir Al-Maraghi as a solution to the identity crisis faced by the millennial generation. The approach used in this study is a tafsir approach with an in-depth content analysis of Tafsir Al-Maraghi’s interpretation of the story of Ashabul Kahfi in Surah Al-Kahfi. The research findings indicate that the story of Ashabul Kahfi contains values of steadfast faith, the struggle to uphold life principles, and the search for self-identity, which align with values of spirituality and belief. These values can provide inspiration for millennials in overcoming the challenges of their identity crisis. The implication of this study is the importance of applying the values of steadfast faith and self-identity search in religious education and character development to shape a generation with firm life principles and a clear direction in facing life’s challenges in the modern era.